Antimicrobial and biological effects of ipemphos and amphos on bacterial and yeast strains - Öztürk, AI; Yilmaz, Ö; Kirbag, S; Arslan, M (John Wiley & Sons Ltd, 2000)
In this study, the antimicrobial effects of monophosphazenes such as SM ipemphos and amphos were examined on bacterial and yeast strains. In addition, the biological effects of these compounds were tested on the lipid level of Saccharomyces cerevisiae and Candida albicans cells. The SM has an antimicrobial effect on the bacterial and yeast strains within the range of 100 and 1500 mu g. When the concentration was increased, the inhibition zone expanded on the growth media (p < 0.01; p < 0.001). The ipemphos did not affect the bacterial and yeast cells in the 100 and 600 mu g range. In addition, the amphos did not show an antimicrobial effect on the bacterial cells between 100 and 300 mu g or on yeast cells at any of the administered concentrations. In vitro media, the biological effects of these molecules were compared with vitamin E, melatonin and fish oil on the yeast cells. We have found that monophosphazenes have growth effects on the cells in vitro media. The lipid level of S. cerevisiae cells was decreased by 300 mu g doses of vitamin E, fish oil, and ipemphos (respectively; p < 0.05, p < 0.01, and p < 0.001). In addition, the lipid levels of the same yeast cells were depressed by 1000-mu g doses in all supplemented groups. However, it was observed that the highest decrease in lipid level of S. cerevisiae cells occurred in the amphos group (p < 0.001). The lipid levels of the C. albicans cells were significantly reduced (p < 0.01) by 300 mu g of amphos and melatonin. In contrast, the vitamin E and fish oil significantly raised (p < 0.01; p < 0.001) the lipid level of the same yeast cell, as compared with the control. In addition, the lipid level of these cells was increased by administration of 1000 mu g vitamin E, and melatonin (p < 0.01). In conclusion, while high concentrations of ipemphos and amphos have an antimicrobial effect on bacterial and yeast cells, amphos did not affect the yeast cells. While ipemphos and amphos increased cell growth in media, they reduced the lipid level of C. albicans and S. cerevisiae. In addition, the antioxidants such as vitamin E, melatonin, and fish oils affected the lipid level of yeast cells. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: monophosphazenes; antimicrobial and biological effects; vitamin E; melatonin; fish oil; bacterial and yeast cells; lipid content